Theoretical concept of conciliation procedure organization in the civil law processes in the dynamics of types of proceedings change - Zdrok, Oksana N. (Journal of the Belarusian State University. Law, 2019)
It is proved that the system of views on the principles and methods of organization of conciliation procedures in civil process depends on the type of proceedings. In this case, the highest priority is typing, depending on the dominant socio-political concept of the state. The author analyzes the changes that have taken place in the judicial branch concept of reconciliation in the transition from liberal to social justice type and occur at present in a number of jurisdictions in connection with the transition to a new postsocial proceeding type. For each of these types of proceedings the author defines the relevant principles and features of the legal regulation of the organization of conciliation procedures, which can serve as a guide when designing changes in civil procedure legislation on the issue of reconciliation of the parties.
Keywords: conciliation; the civil law process; the types of civil proceedings; the liberal type of proceedings; social justice type; postsotsialny trial type; the settlement agreement; mediation; mediation is delegated; the world court